Interleukin-4 and -13 gene expression profiles in immune-related bullous pemphigoid indicate efficacy of IL-4/IL-13 inhibitors - Arnold, Lisa; Morak, Monika; Kramer, Nora; Berking, Carola; Schefzyk, Matthias; Hassel, Jessica C.; Ziemer, Mirjana; French, Lars E.; Gutzmer, Ralf; Nashan, Dorothee; Heinzerling, Lucie (Cancers, 2025)
Background/Objectives: Cutaneous side effects are the most common immune-related adverse events (irAEs) caused by immune checkpoint inhibitors (ICIs) and affect 70-90% of patients. Besides diverse types of exanthema, rare skin toxicity includes bullous dermatoses in 0.3% of cases. Systemic steroids are the first-line treatment for immune-related bullous pemphigoid (irBP); however, some cases are corticosteroid-resistant. IrBP is one of the irAEs most frequently chronic and associated with long-term steroid use. However, steroids may interfere with tumor response. Therefore, alternative treatment strategies for irBP are desperately needed. Dupilumab, a monoclonal antibody blocking the receptor binding of interleukin-4 (IL-4) and interleukin-13 (IL-13), has been successfully used to treat spontaneous forms of bullous pemphigoid (BP). In this study, we analyzed the gene expression profiles of BP and irBP. Patients and Methods: A retrospective multicenter study evaluated the gene expression profiles of irBP and BP in comparison to healthy controls. Gene expression analyses of skin biopsies were performed using NanoString technology from patients with BP (n = 17), irBP (n = 19), and healthy skin (n = 24) after the patients had consented to participate in this study, and differentially expressed genes (DEGs) were determined using Rosalind software. Results: Compared to healthy skin, BP showed 167 DEGs, and irBP revealed 99 DEGs. Some of the DEGs from irBP and BP vs. healthy skin overlapped. Specifically, IL-4- and IL-13-associated genes were upregulated in both irBP and BP compared to healthy skin. Interestingly, expression profiles of BP vs. irBP also showed 13 DEGs. Conclusions: These findings suggest a possibility for therapeutic efficacy of IL-4 and IL-13 inhibitors in the treatment of irBP.
Gesehen am 27.10.2025